2019
DOI: 10.5387/fms.2018-12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of ramucirumab plus paclitaxel for unresectable and recurrent gastric cancer

Abstract: Introduction Recently in Japan, Ramucirumab (RAM) became the first antiangiogenic agent to be approved for secondline treatment of gastric cancer. In the present study, we aimed to evaluate the efficacy and safety of RAM plus paclitaxel (PTX) in patients with unresectable and recurrent gastric cancer in our institution. Patients and Methods The subjects were 11 patients with unresectable and recurrent gastric cancer who received RAM plus PTX as a secondor laterline treatment at our hospital between June 2015 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…In Japan, ramucirumab treatment, as a single agent or in combination with paclitaxel, has been assessed for patients with advanced gastric cancer with or without disease progression after first-line therapy in several real-world clinical practice settings [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Results appear to be consistent with those from the RAINBOW and REGARD trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, ramucirumab treatment, as a single agent or in combination with paclitaxel, has been assessed for patients with advanced gastric cancer with or without disease progression after first-line therapy in several real-world clinical practice settings [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Results appear to be consistent with those from the RAINBOW and REGARD trials.…”
Section: Resultsmentioning
confidence: 99%
“…Results appear to be consistent with those from the RAINBOW and REGARD trials. These studies included patients with large amounts of ascites [ 44 ], in patients categorized as elderly [ 46 , 47 , 49 , 52 ], and in those with liver metastases [ 55 ]. Finally, in Korea, patients enrolled in an expanded access program (EAP) received ramucirumab in combination with paclitaxel or with ramucirumab monotherapy [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…When a tumor exceeds 2 mm 3 , tumor cells can secrete a variety of cytokines to promote angiogenesis [5]. Several studies have also demonstrated that antiangiogenic therapy efficiently prolongs survival in patients with advanced GC [6,7].…”
mentioning
confidence: 99%